Exploring relationships between coursework and examinationmarks: A study from one School of Pharmacy - Murdan, Sudaxshina (Pharmacy Education, 2021)
This study was conducted in order to investigate relationships, if any, between examination and coursework performances,following the observation that a significant number of M.Pharm students achieved high coursework marks during a semester,but then performed poorly in the end-of-semester examinations. Given that the two assessment modes generally tested the same knowledge base and skills, it was thought that a diligent and proper conduct of coursework (which would attract highmarks) would enhance learning which would, in turn, be reflected in a good examination performance. To explore correlations between the two modes of assessment, the marks of students in all 4 years of the M.Pharm degree for a particular academic session were compared and the coursework and examination requirements as well as the factors that could contribute to differences in assessment scores were analysed. Coursework marks were found to be higher than examination ones and while the examination results ranged from fails to first class, the coursework marks were clustered, mostly between 60 and 80%.Pearson analysis revealed only a weak correlation between coursework and examination marks of individual students. The strength of the correlation depended on the year of study, whether the module was a core or an optional one and on the nature of the coursework. In this paper, the findings and the contributing factors are discussed. In addition, suggestions on ways of diverting student focus from coursework marks to the learning event are made.